Cryptogames as Drivers for Blockchain Application Development - Harviainen, J. Tuomas; Serada, Alesha; Sihvonen, Tanja (Springer, 2022)
In this chapter, we outline reasons why cryptogaming, like cryptocurrencies in general, is an area of special interest for blockchain research. We suggest that cryptogaming is a field that drives forward the development of blockchain applications. Games require continuous interest, added value through interaction, and sufficient content in order to stay viable as a business model. They therefore challenge the ways in which we commonly view blockchains as first and foremost trust technologies and sidesteps from traditional banking, contracts and insurance, and call us to envision a much wider application of the technology than is currently being discussed in both popular media and research.
Keywords: blockchain; cryptogames; Non-fungible tokens; Value propositions; fi=Viestintätieteet|en=Communication Studies|